Fixed-dose gabapentin augmentation in the treatment of alcohol withdrawal syndrome: a retrospective, open-label study. (2nd January 2020) - Andaluz, Alex; DeMoss, Dustin; Claassen, Cynthia; Blair, Somer; Hsu, Jennifer; Bakre, Sulaimon; Khan, Mehreen; Atem, Folefac; Rush, A John
ABSTRACT: Background : Lorazepam use in the treatment of alcohol withdrawal syndrome (AWS) is not without risk. Objective : This study compares AWS outcomes using a standard, symptom-triggered lorazepam dosing protocol (control group) and symptom-triggered lorazepam dosing augmented with a gabapentin loading dose and taper (GABA group). Methods : Consecutive, non-randomized adults (n = 982; 64.0% male) undergoing treatment for AWS were included in this retrospective, open-label study. Symptom-triggered lorazepam dosing was informed by scores on the Clinical Institute Withdrawal Assessment-Alcohol, revised (CIWA-Ar). Gabapentin augmentation utilized an initial loading dose (900 mg) and a three-day taper. Outcomes included average symptom severity per treatment hour and average lorazepam dose per treatment hour. Average time in the protocol by group, stratified by highest CIWA-Ar score, was examined as a secondary outcome. A priori group differences were controlled statistically. Results : GABA patients were older and exhibited somewhat more severe withdrawal symptoms than controls. After controlling for confounders, gabapentin augmentation did not significantly lower average lorazepam dosing per treatment hour or withdrawal symptom severity per treatment hour. Compared to controls, overall withdrawal symptoms diminished somewhat more rapidly for GABA patients experiencing low or moderate-level withdrawal symptoms; however, severe withdrawal symptoms remitted more slowly in the GABA group. Results should be interpreted in light of the uncontrolled nature of group assignment and other confounders. Conclusions : Compared to symptom-triggered lorazepam dosing alone, gabapentin augmentation did not produce better outcomes during treatment of acute AWS. These results do not support the use of scheduled gabapentin as an augmentation to benzodiazepines during inpatient treatment of AWS.